Bad guys: America's most wanted in their own words - Baker, Mark (Simon & Schuster, 1996)
Presents the stories of hustlers, con artists, drug dealers, burglars, and others, who describe their starts in crime, the day-to-day lives, their criminal activities, and the trials and rituals of prison life. By the author of Cops. 25,000 first printing. They lie, steal, kill and destroy. Cops chase them, Hollywood glamorizes them, and shrinks try to figure them out. Now, America's bad guys tell their own stories, from their childhoods to how they chose their victims to how they survive in prison. Mark Baker, the bestselling author of Nam and Cops, has gone behind the lines to find out why today's criminals started and why they won't stop. Their gritty, compelling tales are sometimes shocking, sometimes funny, and always bad to the bone.